Play in Special Education: Teachers' Perspectives and Practices - Basaran, Mehmet; Soylemez, Bilal (Routledge Journals, Taylor & Francis Ltd, 2026)
This study examines the perspectives of special education teachers working in early childhood settings on play. Data collected through interviews with 43 teachers employed at a state-run special education institutions located in Eastern T & uuml;rkiye were analysed through content analysis. The findings indicate that teachers preferred physical, object, symbolic, and skill-building types of plays. While most plays were used in both individual and group settings, traditional, symbolic, and skill-building plays were predominantly preferred in group plays. In individual play, cards were frequently used, whereas balls were commonly used in group play. The duration of individual plays typically ranged from 10 to 20 minutes, whereas group plays often lasted longer. The challenges faced by teachers were categorised into those related to children's developmental characteristics and arising from teacher- or institution-related factors. The role of play in supporting learning, social development, motor skills, and communication in special education was emphasised. The study recommends providing teachers with training in play-based education and expanding research on play for children with specific special needs.
Keywords: Early Childhood Period; Play; Special Education; Teachers' Perspectives